The improvement of the technical exploitation of automobiles - Mickūnaitis, Valentinas; Nagurnas, Saulius (Transport, 2002)
This article analyses the factors that considerably influence the efficiency of automobile technical exploitation. It has been noted that automobile technical exploitation is basically determined by the following factors: the system and organizational level of automobile technical maintenance and repairs; the level of service basis; qualification of the staff; the level of stock and supply; the structure and age of automotive fleet and conditions of exploitation. This article presents the analysis of the first factor. The factor is significant enough and does not involve big investments. A theoretical analysis of the system of automobile technical maintenance and repair has been carried out. According to the nature of automobile technical maintenance and repairs two strategies are possible: the planned-preventive and the mixed type. Applying the first strategy the exact number of operations is being planned ahead, but the amount of work remains unknown. According to the second strategy the technical condition of an automobile has to be checked before starting technical maintenance and repair and only then the exact number of operations can be defined. The second strategy makes it possible to save spare parts, materials and time. This strategy, however, can be applied to the automobiles that are in good technical condition. The analysis of automobile technical maintenance and repair organization has shown that in order to improve the efficiency of automobile technical maintenance and repair the laws of mass service theory should be applied.First Published Online: 19 Dec 2011